Packaging and storage studies on coconut residue flour and protein enriched coconut residue flour - Yao, Lissette Faye
The study was conducted with the main objective of determining packaging and shelf life stability of coconut residue flour and protein enriched coconut residue flours, which were determined using Proximity Equilibrium Cell (PEC), exhibited sigmoidal curves. The critical moisture content was found to be 8.5% (dry basis) for coconut residue flour and 4.0% (dry basis) for protein enriched coconut residue flour. Two packaging materials selected for each product were 0.003 and 0.004 in. Low Density Polyethylene (LDPE). The shelf life of the products in these packaging materials were estimated using Half-Value Period (HVP) method. Result showed that both packaging materials can effectively protect coconut residue flour and protein enriched coconut residue flour for at least 1 year under average ambient conditions in the Philippines of 28°C and 81% RH.